Performance of Seven SARS-CoV-2 Self-Tests Based on Saliva, Anterior Nasal and Nasopharyngeal Swabs Corrected for Infectiousness in Real-Life Conditions: A Cross-Sectional Test Accuracy Study - Homza, Miroslav; Zelena, Hana; Janosek, Jaroslav; Tomaskova, Hana; Jezo, Eduard; Kloudova, Alena; Mrazek, Jakub; Murinova, Vera; Madar, Rastislav (Diagnostics, 2021)
Many studies reported good performance of nasopharyngeal swab-based antigen tests for detecting SARS-CoV-2-positive individuals; however, studies independently evaluating the quality of antigen tests utilizing anterior nasal swabs or saliva swabs are still rare, although such tests are widely used for mass testing. In our study, sensitivities, specificities and predictive values of seven antigen tests for detection of SARS-CoV-2 (one using nasopharyngeal swabs, two using anterior nasal swabs and four using saliva) were evaluated. In a setting of a high-capacity testing center, nasopharyngeal swabs for quantitative PCR (qPCR) were taken and, at the same time, antigen testing was performed in accordance with manufacturers' instructions for the respective tests. In samples where qPCR and antigen tests yielded different results, virus culture was performed to evaluate the presence of the viable virus. Sensitivities and specificities of individual tests were calculated using both qPCR and qPCR corrected for viability as the reference. In addition, calculations were also performed for data categorized according to the cycle threshold and symptomatic status. The test using nasopharyngeal swabs yielded the best results (sensitivity of 80.6% relative to PCR and 91.2% when corrected for viability) while none of the remaining tests (anterior nasal swab or saliva-based tests) came even close to the WHO criteria for overall sensitivity. Hence, we advise caution when using antigen tests with alternative sampling methods without independent validation.